Students’ Activities in Learning with Problem Based Learning Based Module to Enhance Students’ HOTS on the Subject of Straight Line Equations - Imelda Imelda; Dewi Anzelina (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This research begins with the observation of researchers of the activities of students who are still passive when participating in learning in accordance with the 2013 curriculum and do not prioritize students' high order thinking skills. Passive student activities are seen in the core activities of learning because in the core activities students are required to develop existing knowledge in themselves. Thus, the purpose of this study is to produce learning that makes students active. The solution to this problem is the implementation Problem Based Learning (PBL) based module covering Higher Order Thinking Skills (HOTS) questions. The research method used was descriptive qualitative research. The technique used to collect data is a non-test technique, namely the observation sheet of student activities. Observation material consists of 4 aspects, namely observation on preliminary activities, core activities, closing activities and time management. The results obtained are active students during the learning of the subject of straight line equationswith module based on PBL obtained from 7 meetings is 82%, which means that student activities during learning with the problem based learning mathematics learning module on the subject of straight line equations are in the very good category